An Origin of Sportsmanship: A Socio-historical Reflection - NAKAE, Keiko (Japan Journal of Sport Sociology, 2006)
This article examines tournament in Middle Ages, which was not examined in Elias's analysis of the origin of sports from his cultural sociological perspective. This study shows that the sports and sportsmanship, which have been supposed to be invented in modern Britain, actually evolved in the games of tournament. Tournament is the one and only sport that could attract broad social attention in Europe in the Middle Ages. The transformation of the style of this particular competition is consistent with maturing morals of knights and the process of development of mechanisms that forced knights to keep violence under control. This article examines this process from a socio-historical perspective. It is true that this moralistic world-respect for lives, restraint on private desire, contribution to the public, and protection of the weak-could not reform reality of feudal society in the Middle Ages. However, it created a peculiar form of love, namely courtly love, and the great popularity of knight stories and tournament inscribed it into the European culture. It survived in the European spirit long after the Middle Ages. Later, when English gentlemen stratum was urged to redefine their identity in the particular political and cultural situation in modern Britain, they rediscovered and reconstructed the moralistic world that was dreamed of in the tournament game in the past. In conclusion, this article shows that ‘sportsmanship’ is a unique European concept. Since sportsmanship can never be a universal idea, we must be careful about its application to diverse cultures that have developed unique forms of training social bodies.